Willingness to Pay for Individual Greenhouse Gas Emissions Reductions: Evidence from a Large Field Experiment - Johannes Diederich; Timo Goeschl (University of Heidelberg, Department of Economics, 2011)
In the climate policy debate, a rhetoric has evolved that attributes a high potential to "voluntary climate action". We turn to the population of Germany, the fourth largest cumulative GHG emitter, to obtain an Internet-)representative estimate of the individual willingness to abate one ton of CO2, the equivalent of 10 percent of annual per-capita CO2 emissions. The estimate derives from a large-scale (n=2,440) framed field experiment in which subjects choose between a guaranteed reduction of one ton of EU CO2 emissions and a randomly drawn cash award between exteuro2 and exteuro100. At exteuro6.30, estimated mean WTP is considerably lower than prior hypothetical or non-representative estimates. Median WTP is non-positive. The almost bimodal nature of WTP in the population has important policy implications.
urn:nbn:de:bsz:16-opus-125433
Keywords: 330; climate change mitigation; field experiment; voluntary climate action; willingness to pay; Klimaschutz; Treibhausgas-Emissionen; Umweltbewusstsein; Zahlungsbereitschaftsanalyse; Feldforschung; Deutschland